Hydrogenation of TixFe2-x-based alloys with overstoichiometric Ti ratio (x = 1.1, 1.15 and 1.2). (8th November 2021) - Ulate-Kolitsky, E.; Tougas, B.; Huot, J.
Abstract: The hydrogenation behavior of Tix Fe2-x +4 wt% Zr alloys, x = 1.1, 1.15 and 1.2 has been investigated. All compositions presented a multiphase microstructure with a TiFe-matrix along with a secondary Ti2 Fe-like phase and a Ti-rich BCC phase. The phase fraction varied with "x". The increase of titanium abundance makes the alloy more stable, but this comes with a loss of hydrogen capacity. The formation of stable hydrides (Ti2 FeHx and FCC) by the secondary phases is reported. The full capacity according to the Rietveld refinement data is calculated. The contribution of each phase matches well with the reversible capacity measured experimentally. The results shown and discussed give insight into the hydrogenation properties of the secondary phases and their effect on a TiFe-based alloy. Highlights: All samples presented good activation kinetics at RT and 20 bar of hydrogen. The stability of the alloy increases with x however reversible capacity is reduced. Ti2 Fe-like phase forms a stable hydride with a calculated H/M between 4 and 3.